PENGARUH PERSEPSI SISWA TENTANG APLIKASI PEMBELAJARAN ONLINE DAN BELIEF MATHEMATIC TERHADAP HASIL BELAJAR MATEMATIKA PADA MASA PANDEMI COVID-19 - Masnani Masnani; Ma'rufi Ma'rufi; Muhammad Ilyas (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
The Covid-19 pandemic forced the learning system requires online-based learning which has several challenges not only for teachers but also students and their parents. This pandemic makes students tend to be degraded in terms of mentality, confidence in their abilities and accessibility in the use of appropriate learning applications. Hence, this study aims to determine the partial and simultaneous effect of students' perceptions on the mathematics learning outcomes of fifth graders using ex-post facto method. The research population is all students of SDN in Malili District. Then a sample of 80 students was drawn by cluster random sampling. The research instrument used was a test instrument for learning outcomes and a mathematical belief questionnaire as well as a student perception questionnaire about online learning applications which analyzed descriptively and inferentially using multiple tests. The results of this study indicate that students' perceptions of online learning applications and Mathematics students' beliefs have a positive effect on students' mathematics learning outcomes at SDN Malili District with a determination of 42.7% and 51.8%, respectively. Students' perceptions of online learning applications and mathematical beliefs simultaneously have a positive effect on students' mathematics learning outcomes with a determination of 61.8%. As a result of this research, there should be further development in complementary dimensions in the form of learning enrichment and remedial applications.